2017
DOI: 10.1002/clc.22802
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of lung function in stable heart failure outpatients

Abstract: Background This study investigated the impact on all‐cause mortality of airflow limitation indicative of chronic obstructive pulmonary disease or restrictive spirometry pattern (RSP) in a stable systolic heart failure population. Hypothesis Decreased lung function indicates poor survival in heart failure. Methods Inclusion criteria: NYHA class II‐IV and left ventricular ejection fraction (LVEF) < 45%. Prognosis was assessed with multivariate Cox proportional hazards models. Two criteria of obstructive airflow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
1
2

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 40 publications
2
28
1
2
Order By: Relevance
“…Moreover, a smaller community‐based sample of older persons with MetS and DM showed MetS and abdominal obesity, but not DM, to be independently associated with restrictive lung disease . Also, although HF risk as a consequence of poor lung function has not previously been reported in MetS and DM patients, others have reported on increased mortality associated with chronic obstructive pulmonary disease (COPD) or restrictive spirometry pattern in patients with HF …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, a smaller community‐based sample of older persons with MetS and DM showed MetS and abdominal obesity, but not DM, to be independently associated with restrictive lung disease . Also, although HF risk as a consequence of poor lung function has not previously been reported in MetS and DM patients, others have reported on increased mortality associated with chronic obstructive pulmonary disease (COPD) or restrictive spirometry pattern in patients with HF …”
Section: Discussionmentioning
confidence: 97%
“…26 Also, although HF risk as a consequence of poor lung function has not previously been reported in MetS and DM patients, others have reported on increased mortality associated with chronic obstructive pulmonary disease (COPD) or restrictive spirometry pattern in patients with HF. 27 Additionally, other Cardiovascular Health Study investigations have demonstrated the association of smoking with impaired FEV 1 / pulmonary function and increased risk of atherosclerosis in the elderly 28,29 ; however, other Cardiovascular Health Study studies showed a small association of reduced FEV 1 and FVC with increased risk of CHD outcomes after excluding cigarette smokers and those with lung diseases known to reduce lung function. 30 In our prior NHANES III study, lower FVC did not add to risk of overall mortality among those with only DM 12 ; in our current study, higher FVC or FEV 1 was related to lower risk of CHD in those with DM and HF in those with MetS, but not stroke in either condition.…”
Section: Discussionmentioning
confidence: 99%
“…The FEV 1 can be influenced by HF status 37 that can mimic obstruction 24 resulting in approximately a quarter of patients with HF but without COPD having reduced FEV 1 , 10,38 leading to measurement error of COPD severity. Furthermore, where there is an imbalance in the reduction of FEV 1 and forced vital capacity as a consequence of pulmonary congestion, a spurious obstructive pattern can occur, resulting in misdiagnosis of COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Johnston et al (2008) выявили, что рестриктивное ограничение воздушного потока встречается у 10 % людей в общей популяции, в когорте пациентов с ХСН частота встречаемости была больше и составила 39 % [2]. Прогностическое значение обструктивных и рестриктивных нарушений у стабильных пациентов с ХСН (n=573) изучено Plesner et al (2017), показавшими, что при ХСН независимо от типа респираторных нарушений наблюдается увеличение смертности от всех причин [3]. Согласно данным литературы смешанные обструктивно-рестриктивные изменения отмечаются при ХСН в сочетании с хронической обструктивной болезнью легких (ХОБЛ) [4].…”
Section: For Citation: Gazizyanova Vm Bulashova Ov Hazova Ev unclassified
“…Изучение респираторной функции легких с учетом величины ФВ проводилось Plesner et al (2017), которые в результате наблюдения за пациентами с ХСН OO-OV ФК с ФВ ЛЖ <45 % (n=573, 4,7 лет) выявили ограничение воздушного потока по обструктивному типу и величину ФВ ЛЖ в качестве предикторов смертности от всех причин в отличие от пациентов с ХСН без бронхиальной обструкции (ОР=2,07; 95 % ДИI: 1,45-2,95; р<0,01 и ОР=0,97; 95 % ДИI: 0,96-0,98; р<0,001 соответственно). В то же время рестриктивное ограничение воздушного потока, а также смешанные нарушения функции дыхания ассоциировались с повышенным риском смерти (ОР=1,67; 95 % ДИI: 1,10-2,53; р=0,02 и ОР=2,09; 95 % ДИI: 1,30-3,35; р<0,01 соответственно) [3]. В исследовании SHOFT (2015) снижение ФВ ЛЖ являлось основным предиктором неблагоприятного прогноза у пациентов с СН (n=6505) [6].…”
Section: For Citation: Gazizyanova Vm Bulashova Ov Hazova Ev unclassified